Andes Basin Focal Project - Mulligan, M.; Rubiano, J.; Hyman, Glenn G.; Gabriel Leon, J.; Saravia, Miguel; White, D.; Vargas, V.; Selvaraj, Michael Gomez; Andrew Farrow, C.B.; Alexander Marin, J.; Lucia Pulido, O.; Ramírez, A.; et al. (CGIAR Challenge Program on Water and Food, 2009)
The CPWF Basin Focal Project for the Andes system of basins worked with a range of local stakeholders to develop a better understanding of the mechanisms for improving the productivity of water in the Andes. We considered productivity in broad terms as the productivity of energy (HEP), food and fiber (agriculture) and livelihoods (industry, transport and benefit sharing such as Payments for Environmental Services schemes (PES)). In addition to the compiled data bases and analyses on poverty and institutions, one of the key deliverables of the project was the development and deployment of the AguAAndes policy support system (PSS). This integrates analyses of water availability and productivity within the local environmental and policy context. It is a web-based policy support system combining an extensive spatial database with process-based models for hydrology, crop production and socio-economic processes. It is intended to allow analysts and decision makers to test the potential onsite and offsite impacts of land and water management decisions in terms of their ability to sustain environmental services and human wellbeing. Interventions and recommendations for future actions on water and food in the region are presented.